2012
DOI: 10.1021/la203988m
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Study of the Deposition of (Ultra)thin Organic Phosphonic Acid Layers on the Oxide of Aluminum

Abstract: The interest in self-assembling monolayer deposition on various oxide substrate surfaces is steeply increasing in the last decades. Although many studies are being performed, literature does not come with a general insight in the adsorption of these layers on oxide surfaces. Also for the deposition of phosphonic acids on aluminum oxides, there is no global consensus. In this paper, we present an original in situ analysis in order to eludicate the real layer formation mechanism. First of all, the state of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…PAs on Al2O3 are also relevant systems. Atomic force microscopy (AFM) and ellipsometry data for PA-modified Al2O3 surfaces were reported by Hauffman et al 30,31 In situ AFM shows fast island formation at the beginning of deposition followed by gap filling. The islands then grow further before the monolayer fully covers the surface.…”
Section: Introductionmentioning
confidence: 91%
“…PAs on Al2O3 are also relevant systems. Atomic force microscopy (AFM) and ellipsometry data for PA-modified Al2O3 surfaces were reported by Hauffman et al 30,31 In situ AFM shows fast island formation at the beginning of deposition followed by gap filling. The islands then grow further before the monolayer fully covers the surface.…”
Section: Introductionmentioning
confidence: 91%
“…Aluminum and its alloys are important practical metallic materials and are usually used after suitable surface treatments, such as anodizing and conversion coating. The formation of SAMs has been investigated as a new surface treatment of aluminum for various applications, including improving adhesion between substrates and paints, and biocompatibilities . SAMs are also introduced on oxidized aluminum surfaces with nanotextures for superhydrophobicity and superoleophobicity .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that an anodized aluminum surface coated with fluorinated alkyl phosphonic acids showed higher contact angles for water and organic liquids in comparison with the alkylsilanes with the same alkyl groups, although the reason was not clarified . Although there are some advantages of phosphonic acids for formation of SAMs on aluminum and several studies on phosphonic acid‐based SAMs on aluminum have been carried out, the formation of SAMs has not been fully understood. Recent in situ analysis revealed island growth of phosphonic acid molecules on aluminum oxide, suggesting that a monolayer is not always formed.…”
Section: Introductionmentioning
confidence: 99%
“…However, Hauffman et al . observed multilayer of phosphonic acid molecules on the Al surface deposited from water solution by AFM and ellipsometry, shown by three growth zones including island growth, island coalescence and new island growth. In addition, on the polar mica surface which is similar to oxide film of aluminum, it is possible to deposit self‐assembled vertical bilayers of simple linear phosphonic acid molecules by spread coating technique, where a solution droplet is deposited on a surface and blow dried with an inert gas .…”
Section: Resultsmentioning
confidence: 97%